+0  
 
0
173
1
avatar

(h * c) / ((r/x*x)-(r/y*y)) = f

 

 

Wie kann ich diese Formel nach y auflösen?

 23.01.2021
 #1
avatar+2962 
+1

\(\frac{h \cdot c}{\frac{r}{x^2}-\frac{r}{y^2}} = f \ \ \ | \cdot Nenner \\ hc = f \cdot (\frac{r}{x^2}-\frac{r}{y^2}) \ \ |:f \\ \frac{hc}{f} = \frac{r}{x^2}-\frac{r}{y^2} \ \ \ |-\frac{r}{x^2} \\ \frac{hc}{f} - \frac{r}{x^2} = - \frac{r}{y^2} \ \ \ | \cdot (-1) \\ \frac{r}{x^2} - \frac{hc}{f} = \frac{r}{y^2} \ \ \ | ^{-1} \\ \frac{1}{\frac{r}{x^2} - \frac{hc}{f}} = \frac{y^2}{r} \ \ \ | \cdot r \\ \frac{1}{\frac{r}{x^2} - \frac{hc}{f}} \cdot r = y^2 \ \ \ | \sqrt. \\ \pm \sqrt{\frac{1}{\frac{r}{x^2} - \frac{hc}{f}} \cdot r} = y\)

 

Ich hoff' das ist verständlich so ;)

 23.01.2021

41 Benutzer online

avatar
avatar